Soft solid crystal material, solid electrolyte membrane, all-solid-state lithium metal battery and preparation method of all-solid-state lithium metal battery
By developing a soft solid crystal material Li(C5H6N2)2BF4, the problem of insufficient performance of existing solid electrolytes in lithium-ion batteries is solved, and the comprehensive performance of high ionic conductivity, chemical stability and processing convenience is achieved.
Patent Information
- Application Number
- CN202311016035.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-25
AI Technical Summary
Existing solid electrolytes are difficult to meet the comprehensive performance requirements of high ionic conductivity, chemical stability and processing convenience in lithium-ion batteries.
A soft solid crystalline material Li(C5H6N2)2BF4 was developed, which was prepared by heating reaction of lithium tetrafluoroborate and glutarnitrile. The material can undergo solid-liquid phase transformation at a specific temperature to form an electrolyte membrane with ion migration channels.
This material has high thermal stability, good melt casting and self-healing properties, taking into account the advantages of polymer solid electrolytes and inorganic solid electrolytes, and can form a uniform film material and improve the ionic conductivity and chemical stability of the battery.
Smart Images

Figure CN119504495A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel electrolytes, and in particular relates to a soft solid crystalline material and a preparation method and application thereof. Background Art
[0002] Traditional electrolyte materials are widely used in lithium-ion batteries, such as liquid electrolytes and polymer electrolytes. However, these materials have some defects that limit the stability and performance of the battery. Liquid electrolytes may leak or produce thermal runaway risks, and polymer electrolytes also have problems such as low ionic conductivity and high internal resistance.
[0003] All-solid-state batteries are a promising electrochemical energy storage device that can overcome many of the shortcomings of traditional liquid batteries, including the problems of easy leakage of liquid electrolytes, flammability and explosion, and low stability. Solid electrolytes are an important component of all-solid-state batteries. Replacing organic liquid electrolytes and porous polymer separators with solid ion conductors is expected to achieve higher safety and energy density. Practical solid electrolytes have many performance requirements, such as high ionic conductivity, high electrochemical stability, high thermal stability, and chemical stability of the electrode-electrolyte interface.
[0004] In recent years, researchers have developed a variety of solid electrolytes, including polymers, polymer gels with non-volatile liquids, and inorganic solid electrolytes. Polyethylene oxide (PEO) is a typical representative of polymer solid electrolytes and is also the most intensively studied electrolyte. PEO has a small dielectric constant in its amorphous state and can dissolve a variety of lithium salts. The ability of PEO to conduct ions is mainly based on the oxygen-assisted hopping mechanism, but this only occurs when the chain segments of PEO are able to move over long distances in the amorphous state. However, PEO is in a semi-crystalline state at room temperature, and its ionic conductivity is less than 10 -6 S / cm.
[0005] Inorganic solid electrolytes have an ion migration number close to 1 and a mechanical strength much higher than that of metallic lithium, making them ideal materials for protecting metallic lithium. The types that are currently being studied include perovskite, sulfide, oxide, etc. Among them, the room temperature ionic conductivity of perovskite solid electrolytes can reach 10 -3 S / cm, but when it comes into contact with lithium, the titanium ions will be reduced and cannot be used directly in lithium batteries. Sulfides have high ionic conductivity and low activation energy at room temperature, but the poor physical contact between sulfide electrolytes and electrode interfaces, poor chemical stability, and more side reactions limit their use. Oxides have a wide electrochemical window, good thermal stability, high mechanical strength, high lithium ion conductivity, and moderate cost; however, their limitations are that they are difficult to process and have poor solid-solid interface compatibility.
[0006] That is, the performance parameters of current solid electrolytes are difficult to meet practical needs. Therefore, developing solid electrolytes with high ionic conductivity is one of the key issues in the development of the next generation of all-solid-state batteries, and it is also a hot spot and difficulty in current research. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a soft solid crystalline material.
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0011] The material molecular formula is Li(C 5 H 6 N 2 ) 2 BF 4 , the structural formula is shown in formula (A);
[0012]
[0013] Among them, the Li atom is connected to the N atom and the alkyl chain, and BF 4 - Anions are free in the surroundings and have ion migration channels.
[0014] As a preferred embodiment of the soft solid crystalline material of the present invention, the material undergoes a solid-liquid phase transition at 60-100°C.
[0015] Another object of the present invention is to provide a method for preparing the soft solid crystalline material.
[0016] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0017] Lithium tetrafluoroborate and glutaronitrile react by heating to obtain a complex solution, and the solution is allowed to stand at room temperature until crystals recrystallize and precipitate, and the obtained precipitate is a soft solid crystalline material.
[0018] As a preferred embodiment of the method for preparing the soft solid crystalline material of the present invention, the molar ratio of lithium tetrafluoroborate to glutaronitrile is 1:4-20.
[0019] As a preferred embodiment of the method for preparing the soft solid crystalline material of the present invention, the heating reaction has a heating temperature of 100 to 200° C. and a heating time of 1 to 12 hours.
[0020] Another object of the present invention is to provide a solid electrolyte membrane, comprising a glass fiber diaphragm and a soft solid crystalline material, wherein the soft solid crystalline material is heated at 60 to 100° C. to become a liquid and then dripped into the glass fiber diaphragm.
[0021] Another object of the present invention is to provide an all-solid-state lithium metal battery, which comprises, from top to bottom, a positive electrode, a lithium negative electrode, and the solid electrolyte membrane as described in claim 6.
[0022] As a preferred embodiment of the all-solid-state lithium metal battery of the present invention, the positive electrode sheet is composited with lithium iron phosphate, polyvinylidene fluoride, carbon black and N-methylpyrrolidone.
[0023] As a preferred solution of the all-solid-state lithium metal battery of the present invention, the stable voltage window of the lithium metal battery is >4.45V, and the conductivity is >0.7mS / cm.
[0024] As a preferred embodiment of the all-solid-state lithium metal battery of the present invention, the capacity retention rate of the lithium metal battery after 100 cycles at room temperature, a charge and discharge range of 2.8V to 3.8V, and a charge and discharge rate of 1C is greater than 93%.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention has developed a new type of soft solid crystalline material with high thermal stability, good melt-castability and self-healing properties. It can undergo solid-liquid phase transition at a specific temperature and has liquid-like fluidity. It can be used as a salt-organic eutectic electrolyte for the preparation of solid-state batteries.
[0027] (2) The soft solid crystalline material of the present invention takes into account the advantages of both polymer solid electrolytes and inorganic solid electrolytes, and can form a more uniform membrane material when coated in liquid form during processing. The resulting battery can obtain good interface contact like a liquid battery, and has both the high ionic conductivity of a polymer solid electrolyte and the high chemical stability of an inorganic solid electrolyte, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is an atomic structure diagram of the electrolyte of Example 1 of the present invention.
[0030] Figure 2 This is a three-dimensional structure diagram of the electrolyte of Example 1 of the present invention.
[0031] Figure 3 This is the XRD diffraction pattern of the electrolyte of Example 1 of the present invention.
[0032] Figure 4 This is the TGA curve of the electrolyte of Example 1 of the present invention.
[0033] Figure 5 This is the DSC curve of the electrolyte of Example 1 of the present invention.
[0034] Figure 6 This is the linear sweep voltammetry curve of the solid-state lithium battery prepared with the electrolyte of Example 1 of the present invention.
[0035] Figure 7 This is a SEM image of the electrolyte of Example 2 of the present invention.
[0036] Figure 8 The cyclic voltammetry (CV) curve of the lithium battery prepared with the electrolyte of Example 2 of the present invention.
[0037] Fig. 9 The lithium ion conductivity test of the solid-state lithium battery prepared with the electrolyte of Example 2 of the present invention.
[0038] Fig.10 The cycle test performance of the solid-state lithium battery prepared with the electrolyte of Example 2 of the present invention.
[0039] Fig.11 This is a charge and discharge curve of a solid-state lithium battery made with the electrolyte of Example 2 of the present invention.
[0040] Fig.12 The cycle test performance of the solid-state lithium battery prepared with the electrolyte of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0044] The crystal material prepared by the present invention is used to prepare a synthetic all-solid-state lithium metal battery according to the following method:
[0045] Preparation of lithium battery separator materials: In a glove box, the soft solid crystalline material is heated at 100°C for 10 minutes to undergo a solid-liquid phase transition and present a solution state. Then 50 μl of the solution is dripped into a commercial Whatman glass fiber separator and allowed to stand for 10 minutes to obtain a solid electrolyte membrane.
[0046] Preparation of positive electrode sheet: After weighing lithium iron phosphate, polyvinylidene fluoride, and carbon black in a mass ratio of 80:15:5, add 0.3mL N-methylpyrrolidone and grind into a uniform slurry. Use a scraper to apply a uniform thickness of electrode slurry on the surface of the current collector, and then dry it in a vacuum oven at 80°C for 24 hours until the solvent is completely evaporated and the electrode surface is completely dry. Then, cut the electrode sheet into a circular electrode with a diameter of 12mm. Finally, transfer it to an argon glove box for use.
[0047] Assembly of lithium battery: Place the stainless steel negative electrode shell, lithium negative electrode, prepared solid electrolyte membrane, positive electrode sheet, stainless steel gasket, stainless steel spring, and stainless steel positive electrode shell in sequence from bottom to top, and apply pressure and fix them on a battery press to obtain an all-solid-state lithium metal battery.
[0048] Example 1
[0049] This embodiment provides a method for preparing a soft solid crystalline material, the material molecular formula of which is Li(C 5 H 6 N 2 ) 2 BF 4 , the structural formula is shown in formula (A);
[0050]
[0051] The specific preparation method is:
[0052] In a glove box with oxygen and water contents below 0.1 ppm, 937 mg of lithium tetrafluoroborate and 4.0 ml of glutaronitrile (the molar ratio of lithium tetrafluoroborate to glutaronitrile is 1:4) were weighed, heated at 165°C for 10 hours, and a lithium salt-organic solvent complex solution was prepared. After standing at room temperature for 1 hour, crystals were recrystallized from the solution to obtain a soft solid crystalline material.
[0053] Figure 1 The atomic structure diagram of the material shows that the material is formed by the connection of Li atoms, nitrogen atoms and alkyl chains, and tetrafluoroborate anions are free around. Figure 2 From its three-dimensional structure diagram, it can be seen that the material contains ion migration channels.
[0054] Figure 3 The XRD diffraction pattern of the material is shown in Figure 2. It can be seen that the XRD pattern of the prepared material is completely consistent with the theoretical simulation pattern, indicating that the prepared material has a high degree of crystallinity and is consistent with the atomic structure arrangement. Figure 1 , Figure 2 Table 1 is the measured data of the crystal structure.
[0055] Table 1
[0056]
[0057] Figure 4 The TGA curve of the material shows that the crystalline material starts to lose mass at 100°C, which proves that it has good thermal stability below 100°C, indicating that it meets the performance requirements of solid-state batteries.
[0058] Figure 5 is the DSC curve of the material. The DSC curve shows the melting point T of the electrolyte. m It is about 55°C, which means that the material can undergo solid-liquid phase transition at a relatively low temperature (60-100°C) and maintain thermal stability.
[0059] Figure 6 This is a linear sweep voltammetric curve of a solid-state lithium battery made with the electrolyte of Example 1 of the present invention. It can be seen that the stable voltage window of the electrolyte is 4.45V, indicating that the lithium battery can operate stably within the working voltage of the lithium iron phosphate positive electrode.
[0060] Example 2
[0061] The difference between this embodiment and embodiment 1 is that the molar ratio of lithium tetrafluoroborate to glutaronitrile is adjusted to 1:20, and the remaining process steps are the same as those in embodiment 1 to obtain the crystalline material of this embodiment. Figure 7 described.
[0062] Figure 7This is a scanning electron microscope image of the crystalline material of Example 2 of the present invention, in which rectangular crystals can be seen interlaced with each other.
[0063] Figure 8 The cyclic voltammetry (CV) curve of the lithium battery prepared with the electrolyte of Example 2 of the present invention, wherein the electrochemical window is 2.5V-4.2V and the scan rate is 0.1mV / s. As shown in the figure, the CV curve shows the redox characteristic peak of lithium iron phosphate, which indicates that the lithium battery prepared in this example has good stability.
[0064] Fig. 9 The lithium ion conductivity of the lithium battery prepared with the electrolyte of Example 2 of the present invention was tested. According to the Arrehenius formula, the lithium ion conductivity was calculated to be 0.7 mS / cm, which was close to that of conventional organic electrolytes.
[0065] Fig.10 The cycle test performance of the lithium battery prepared with the electrolyte of Example 2 of the present invention. The battery charge and discharge range is 2.8V to 3.8V, the test temperature is room temperature, and the charge and discharge rate is 1C. It can be seen that under this condition, the solid-state lithium battery exhibits good cycle stability, and the capacity retention rate after 100 cycles is 93%, and the coulombic efficiency is close to 100%.
[0066] Fig.11 This is the charge-discharge curve of the lithium battery made with the electrolyte of Example 2 of the present invention, and the polarization voltage difference is 0.15V.
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that the heating condition is adjusted to 80°C for 1 hour, and the other process steps are the same as Example 1. A small amount of crystalline product is obtained, and the yield is extremely low. The lithium battery thus prepared has poor cycle stability. This shows that the temperature parameter of the preparation process is important for product synthesis.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium hexafluorophosphate, and the other process steps are the same as those in Example 1 to obtain a lithium salt-glutaronitrile complex solution. However, no solid single crystal product can be obtained during the static recrystallization process, and the liquid state remains. The liquid lithium battery is assembled, and its cycle test performance is as follows: Fig.12 shown.
[0071] Fig.12The cycle test performance of the lithium battery prepared in comparative example 2 of the present invention is shown. The battery charge and discharge range is 2.8V to 3.8V, the test temperature is room temperature, and the charge and discharge rate is 1.0C. It can be seen that after 100 cycles, the coulomb efficiency of the battery is only 75%, and the charge and discharge specific capacity is significantly lower than that of the batteries in Examples 1 and 2, indicating that the type of lithium salt is crucial to the synthesis of the electrolyte of the present invention.
[0072] Comparative Example 3
[0073] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium fluoride, and the remaining process steps are the same as those of Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0074] Comparative Example 4
[0075] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium hydroxide, and the remaining process steps are the same as Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0076] Comparative Example 5
[0077] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium bis(trifluoromethanesulfonyl)imide, and the remaining process steps are the same as those of Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0078] Comparative Example 6
[0079] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium bis(fluorosulfonyl)imide, and the remaining process steps are the same as those of Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0080] Comparative Example 7
[0081] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium bis(trimethylsilyl)amide, and the remaining process steps are the same as those in Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0082] Comparative Example 8
[0083] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium bis(oxalatoborate), and the remaining process steps are the same as those in Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0084] Comparative Example 9
[0085] The difference between this comparative example and Example 1 is that the type of lithium salt is adjusted to lithium difluorooxalatoborate, and the remaining process steps are the same as those of Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0086] Comparative Example 10
[0087] The difference between this comparative example and Example 1 is that the type of organic solvent is adjusted to adiponitrile, and the other process steps are the same as Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0088] Comparative Example 11
[0089] The difference between this comparative example and Example 1 is that the type of organic solvent is adjusted to methylglutaronitrile, and the other process steps are the same as Example 1. After heating, a uniform solution state is presented, but the recrystallization process cannot produce a crystalline product and still maintains a liquid state.
[0090] It can be seen from the results of Comparative Examples 3 to 11 that when any one of the raw materials lithium tetrafluoroborate and glutaronitrile used in the present invention is replaced, a crystalline product cannot be obtained. After heating the raw materials, a uniform solution state is presented, and after recrystallization, the liquid state remains. They are assembled into liquid lithium batteries. The results show that the electrochemical cycle stability is very poor, and the performance is significantly inferior to the all-solid-state lithium battery of the present invention.
[0091] In summary, the present invention has developed a new type of soft solid crystalline material, which is used as a salt-organic eutectic electrolyte for assembling all-solid-state lithium-ion batteries. It has high thermo-electrochemical stability, ionic conductivity, good melt-castability and self-healing properties, and can undergo solid-liquid phase transition at a specific temperature. It has liquid-like fluidity and can obtain good interface contact like a liquid battery. It has the advantages of both polymer solid electrolytes and inorganic solid electrolytes and has great application prospects.
[0092] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A soft solid crystalline material, characterized in that: The molecular formula of the material is Li(C5H6N2)2BF4, and the structural formula is shown in formula (A); 2. The soft solid crystalline material according to claim 1, characterized in that: The material undergoes a solid-liquid phase transition under the condition of 60-100°C.
3. The method for preparing a soft solid crystalline material according to claim 1 or 2, characterized in that: include, Lithium tetrafluoroborate and glutaronitrile react by heating to obtain a complex solution, and the solution is allowed to stand at room temperature until crystals recrystallize and precipitate, and the obtained precipitate is a soft solid crystalline material.
4. The method for preparing a soft solid crystalline material according to claim 3, characterized in that: The molar ratio of lithium tetrafluoroborate to glutaronitrile is 1:4-20.
5. The method for preparing a soft solid crystalline material according to claim 3, characterized in that: The heating reaction, wherein the heating temperature is 100-200° C., and the heating time is 1-12 hours.
6. A solid electrolyte membrane, characterized in that: include, A glass fiber diaphragm, and a soft solid crystalline material as claimed in claim 1.
7. The solid electrolyte membrane according to claim 6, characterized in that: The soft solid crystalline material is heated at 60-100° C. to become liquid and then dripped into the glass fiber separator.
8. An all-solid-state lithium metal battery, characterized in that: include, A positive electrode, a lithium negative electrode, and the solid electrolyte membrane as claimed in claim 6.
9. The all-solid-state lithium metal battery according to claim 8, characterized in that: The positive electrode is obtained by compounding lithium iron phosphate, polyvinylidene fluoride, carbon black and N-methyl pyrrolidone.
10. The all-solid-state lithium metal battery according to claim 8, characterized in that: The lithium metal battery has a stable voltage window of >4.45V and a conductivity of >0.7mS / cm.
11. The all-solid-state lithium metal battery according to claim 8, characterized in that: The capacity retention rate of the lithium metal battery after 100 cycles under the conditions of room temperature, a charge and discharge range of 2.8V to 3.8V, and a charge and discharge rate of 1C is greater than 93%.